SAT0011 An IL-32 Promoter SNP Associated with Lower HDL and Anti-CCP Promoting Atherosclerosis in RA. (9th June 2015) - Heinhuis, B.; Damen, M.; Holewijn, S.; de Graaf, J.; Fransen, J.; Popa, C.; Joosten, L.
Abstract : Background: The association between rheumatoid arthritis (RA) and cardiovascular diseases (CVD) is well established [1]. Interleukin (IL)-32, a highly expressed proinflammatory cytokine in RA [2] might play a key role in both processes. We have recently reported that IL-32 expression is enhanced in human atherosclerotic plaques, while overexpression of IL-32 produced more proatherosclerotic mediators [3]. Interestingly, the expression of IL-32 might be regulated by single nucleotide polymorphisms (SNPs) located in the promoter region of the gene. Objectives: Firstly to determine whether SNP rs4786370 located in the promoter region of IL-32 is associated with IL-32 expression; secondly to investigate possible association of the SNP with several traditional CV risk factors in a control cohort and a group of patients with RA. Methods: HUVEC cells from different donors were used to determine the IL-32 promoter SNP and IL-32 expression. DNA samples from individuals from the Nijmegen Biomedical Study were used to determine the IL-32 promoter SNP by Taqman assay and to associate with different CV risk factors such as lipoprotein profile. Finally, similar associations have been performed using DNA samples and other data from several RA cohorts. Results: HUVEC cells with the TT-genotype displayed more IL-32 expression than the CC-genotype. In the general population cohort, the TT-genotype has been associated with reduced circulating HDL-cholesterol levels. This observation has been also confirmed in several RA cohorts. No differences among genotypes have been observed for TC, TG, LDL, ApoB, glucose, or von Willebrand Factor. Interestingly, rheumatoid factor (RF), ESR, or CRP concentrations were also not different but RA patients bearing the TT-genotype were more prone to be anti-CCP positive. Conclusions: The IL-32 promoter SNP rs4786370 is clearly associated with enhanced IL-32 expression and lower HDL concentrations. In RA patients, the TT-genotype is also associated with anti-CCP positivity. Because both low HDL as well as anti-CCP positivity are linked with higher CVD risk in RA, future studies should reveal whether this IL-32 promoter SNP might be used as a novel CV risk marker. References: Gabriel SE, et al. Survival in rheumatoid arthritis: a population-based analysis of trends over 40 years. Arthritis Rheum 2003;48:54–8. Joosten LAB, et al. IL-32, a proinflammatory cytokine in rheumatoid arthritis. Proc Natl Acad Sci U S A 2006;103:3298–303. Heinhuis B, et al. Towards a role of interleukin-32 in atherosclerosis. Cytokine 2013;64:433–40. Disclosure of Interest: None declared